Phytochelatin Characterization in Commonly Consumed Plant Foods Using Mass Spectrometry-based Metabolomics (P18-122-19). (13th June 2019) - Dennis, Kristine; Liu, Ken; Tran, ViLinh; Liang, Bill; Go, Young-Mi; Jones, Dean
Abstract: Objectives: Phytochelatins (PyCs) are a group of metal-binding compounds formed by plants which could impact bioavailability of essential and toxic metals in the human diet. Liquid chromatography mass spectrometry (LC-MS)-based metabolomics can characterize a diversity of compounds from complex matrices. The aim of this project was to determine chromatographic characteristics of PyCs and their mass spectral signatures using authentic standards and determine if two types of PyCs (PyC2 -Gly and PyC3 -Gly) can be detected in commonly consumed plant foods and validated using chromatographic characteristics and ion dissociation mass spectrometry (MS/MS). Methods: We analyzed PyC2 -Gly and PyC3 -Gly standards using LC-MS (C18 column; 10 minute analysis, positive ionization mode) at 5 different concentrations with 3 sample preparation methods to determine the common adducts, retention times, and optimal sample preparation methods. The most common adducts were selected for MS/MS to determine the characteristic fragmentation patterns. Onion, carrot, tomato, and whole wheat flour samples were analyzed with LC-MS/MS using the optimized sample preparation method and determined chromatographic and ion dissociation characteristics from the PyC standards analysis. Results: For both PyC standards, the most common adducts were identified as follows: M + H > M + Na > M +K > 2M + H > 2M + Na = 2M + K > M + 2H and metabolite features had a retention time of 42 seconds. The fragmentation patterns for PyC2 -Gly and PyC3 -Gly for the M + H adduct ( m/z 538.1272 and m/z 770.1790) were determined by MS/MS. The results show that fragmentation of m/z 538.1272 yielded m/z 231.0433, 334.0525, and 409.0844, and m/z 770.1790 yielded m/z 231.0433, 308.0911, and 641.1358. PyC2 -Gly was detected in all 4 food types with a fragmentation pattern matching the PyC2 -Gly standard while PyC3 -Gly was not detected in these food samples. Conclusions: This project defines chromatographic and mass spectrometry characteristics of PyC2 -Gly and PyC3 -Gly. Using these characteristics, we were able to validate PyC2 -Gly in 4 plant foods. As PyCs may impact metal bioavailability from the diet, optimizing LC-MS detection methods for PyCs in plant foods facilitates future characterization of PyCs in the human diet. Funding Sources: National Institute of Environmental Health Sciences.